Therapy of Inflammatory Bowel Disease using 5-Aminosalicylic Acid, 4-Aminosalicylic Acid and Olsalazine Retention Enemas: Review of Clinical Trials - M. Campieri; P. Gionchetti; A. Belluzzi; C. Brignola; P. Iannone; M. Miglioli; L. Barbara (Canadian Journal of Gastroenterology)
The knowledge that 5-aminosalicylic acid (5-ASA) is the active compound of sulphasalazine and that it acts topically has stimulated the use of 5-ASA containing enemas and ocher similar compounds such as olsalazine and 4-aminosalicylic acid (4-ASA). 5-ASA enemas have been shown to be effective in controlling active disease in clinical trials and have also been shown to be of benefit in prevention of relapses. Olsalazine enemas have not demonstrated significantly better results than placebo 4-ASA enemas are effective but the results obtained have differed as to effective dose